Control de botrytis ( Botrytis cinerea ), con fungicidas en pos cosecha de rosas, en la empresa Royal Flowers - Mulaló. - Amaya Oñate, Edgar Alexander (2021)
Botrytis cinerea is a disease that affects flower buds in export roses, which makes them a non-commercial product, causing significant losses of up to 60% of the harvest and damage to the commercial brand of a product. This research aimed to determine an efficient fungicide to control Botrytis cinerea during the postharvest process of roses at Royal Flowers company, in addition to evaluating the efficiency of the fungicidesand identifying the effective treatment for its control. A completely randomized design was carried out using the statistical software "Infostat" for the evaluation of three fungicides: Prochloraz 0.8cc / l, Fenhexamid + Tebuconazole 1.25cc / l, and Ciprodinil + Fludioxonil 0.7g / l; Tracer 0.15cc / l (Thrips control) was added to each of these, and Agral 0.3cc / l was used as a dispersant in all treatments. Stems of the Pink Floyd variety were selected that entered the postharvest room, whose buds showed symptoms of Botrytis; the fungicide treatments were evaluated with two types of applications, complete immersion of the stems in the solution and spraying through sprinklers in the reception of the postharvest to check if the type of application has effects on the effectiveness of the fungicides; the percentage of affectation was evaluated on the 14 days after the application of the fungi. It was determined that the type of application has a strong influence on reducing the damage caused by Botrytis cinerea in the Pink Floyd rosebuds variety. The results show that the best treatment is the use of the fungicide Ciprodinil + Fludioxonil in immersion, which achieves a percentage of damage of 13.2 ± 5.52% compared to 54.5 ± 10.79% of the control.